2001
DOI: 10.1055/s-2001-17835
|View full text |Cite
|
Sign up to set email alerts
|

Die Metastasenabsiedlung in die Nasennebenhöhlen: Fallmitteilung und Literaturübersicht1

Abstract: The case of an 87-year old man with widespread prostatic cancer is reported. During the autopsy macroscopically visible metastases were found within the frontal sinuses. These tumor masses destroyed the posterior osseous wall of the frontal sinus and formed polypoid bulging masses. In contrast to the macroscopically unaffected mucous membrane of the sphenoid sinus the maceration specimen of the skull base demonstrated a spongious-mossy, osteoplastic metastasis, lining the sphenoid sinus like a tapestry. This a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(24 citation statements)
references
References 35 publications
1
22
1
Order By: Relevance
“…Two cases presented simultaneously in the paranasal sinus and the bony orbit [63, 69]. Clinical manifestations include epistaxis, nasal obstruction, visual disturbances, and facial or intraoral swelling [70, 71]. The maxillary sinus is the most commonly involved sinus followed by the sphenoid sinus, ethmoid, and frontal sinus [70, 72].…”
Section: Discussionmentioning
confidence: 99%
“…Two cases presented simultaneously in the paranasal sinus and the bony orbit [63, 69]. Clinical manifestations include epistaxis, nasal obstruction, visual disturbances, and facial or intraoral swelling [70, 71]. The maxillary sinus is the most commonly involved sinus followed by the sphenoid sinus, ethmoid, and frontal sinus [70, 72].…”
Section: Discussionmentioning
confidence: 99%
“…The mass can be identified as metastatic after histopathological examination of the tissue sample. Malignancies metastasizing to the sinonasal region include, in the order of frequency, RCC, bronchogenic carcinoma, thyroid and breast carcinomas, and prostate tumors (2). Of these metastatic masses, tumors originating from intrapelvic organs are significant due to their ability to paradoxically spread to the head and neck region.…”
Section: Discussionmentioning
confidence: 99%
“…While malignant lesions are rare tumors, metastatic masses are highly rare in this group. To name in the order of frequency, renal cell carcinoma (RCC), bronchogenic carcinoma, thyroid and breast carcinomas, prostate tumors can metastasize to the sinonasal region (2). Particularly RCC is the most common metastatic tumor of this region (3).…”
Section: Introductionmentioning
confidence: 99%
“…A review of 169 cases carcinoma metastasized tothe paranasal sinuses [29,38] revealed that most primary tumors were located in the kidney (40%), followed by the lung, breast, thyroid, and prostate (approximately 10% at each site). The maxillary sinuses were the most commonly affected site, followed by the sphenoid sinuses, the ethmoid sinuses, and the frontal sinuses; in 22% of the cases, multiple sinuses were involved [29,38].…”
Section: Sinonasal Metastasesmentioning
confidence: 99%